2021
DOI: 10.7554/elife.73215
|View full text |Cite
|
Sign up to set email alerts
|

The IRE1/XBP1 signaling axis promotes skeletal muscle regeneration through a cell non-autonomous mechanism

Abstract: Skeletal muscle regeneration is regulated by coordinated activation of multiple signaling pathways. The unfolded protein response (UPR) is a major mechanism that detects and alleviates protein-folding stresses in the endoplasmic reticulum. However, the role of individual arms of the UPR in skeletal muscle regeneration remain less understood. In the present study, we demonstrate that IRE1α (also known as ERN1) and its downstream target, XBP1, are activated in skeletal muscle of mice upon injury. Myofiber-specif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 55 publications
4
19
1
Order By: Relevance
“…While ER stress is the major trigger for the activation of ER stress sensors IRE1α, PERK, and ATF6, accumulating evidence suggests that the UPR pathways can also be activated in the absence of ER stress through crosstalk with other signaling pathways that are activated by cell surface receptors to regulate various cellular responses (55)(56)(57). We recently reported that the IRE1α/XBP1 signaling is highly activated in skeletal muscle in response to injury and that myofiberspecific deletion of IRE1α or XBP1 attenuates muscle regeneration potentially through inhibiting the proliferation of satellite cells in a cell non-autonomous manner (29). However, the cell autonomous role and mechanisms of action of IRE1α in muscle progenitor cells remained unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While ER stress is the major trigger for the activation of ER stress sensors IRE1α, PERK, and ATF6, accumulating evidence suggests that the UPR pathways can also be activated in the absence of ER stress through crosstalk with other signaling pathways that are activated by cell surface receptors to regulate various cellular responses (55)(56)(57). We recently reported that the IRE1α/XBP1 signaling is highly activated in skeletal muscle in response to injury and that myofiberspecific deletion of IRE1α or XBP1 attenuates muscle regeneration potentially through inhibiting the proliferation of satellite cells in a cell non-autonomous manner (29). However, the cell autonomous role and mechanisms of action of IRE1α in muscle progenitor cells remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that the levels of phosphorylated IRE1α (p-IRE1α) protein are drastically increased in injured skeletal muscle of adult mice (29). Pax7 transcription factor is a widely used marker expressed in both quiescent and activated satellite cells (30).…”
Section: Activation Of Ire1α In Muscle Progenitor Cellsmentioning
confidence: 99%
“…Xbp1s mRNA has been identified as a hallmark in many conditions characterized by the formation of insoluble intracellular aggregates such as Alzheimer's [51], Huntington's [52], and metaphyseal chondrodysplasia-type Schmid [53] diseases. IRE1α and its downstream target, XBP1, are activated in the skeletal muscle of mice upon injury [54], and this branch is essential for alleviating protein aggregation related to skeletal disease [55].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, ER stress-induced IRE1 has also been reported to modulate cytokine production differently, including in the production of IL-1β and TNF-α via the activation of glycogen synthase kinase (GSK)-3β and XBP1, respectively [ 113 ]. Finally, IRE1 has been proven to be a key interactor involved in NF-κB activation [ 114 , 115 ] and might have a fundamental role in metabolic syndrome and lipid disorders [ 116 ], regenerative myogenesis [ 117 ], or cardiac diseases [ 118 ]. The upregulation of this IRE1-mediated NF-κB has also been shown to enhance NLRP3 expression in a liver fibrosis model [ 119 ].…”
Section: Discussionmentioning
confidence: 99%